Data about marine area-based management tools to assess their contribution to the UN sustainable development goals - Elena Gissi; Frank Maes; Zacharoula Kyriazi; Ana Ruiz-Frau; Catarina Frazão Santos; Barbara Neumann; Adriano Quintela; Fátima L. Alves; Simone Borg; Wenting Chen; Maria da Luz Fernandes; Maria Hadjimichael; et al. (Data in Brief, 2022)
The dataset presented in this article contains information about marine Area-Based Management Tools (ABMTs) used to assess their contribution to the United Nations 2030 Sustainable Development Goals. Following the scope of the analysis, ABMTs were identified by scrutinizing international and regional legal sources related to ocean management in the fields of marine conservation, fisheries, deep sea bed mining, underwater natural and cultural heritage, environmental conservation, and marine spatial planning. Legal sources were screened to depict the following characteristics of individual ABMTs: i) management objectives; ii) authorities responsible for delivering such objectives; iii) the system of management and planning entailed in the ABMT including the zoning type; and iv) the specific spatial scope and domain each ABMT refer to in vertical depth and horizontal domain. Data were generated through an internal expert elicitation. Experts, initially trained in the data analysis and related protocol, contributed to the data production because of their specific knowledge and experience in ocean management. This dataset represents a unique source of information for advancing research about monitoring and assessment of the achievement of sustainable development goals that encompasses different types of ABMTs.